FITTING TEST OF RELIGIOUS-ORIENTATION MEASUREMENT MODEL - Sumanto Sumanto (Jurnal Psikologi Tabularasa, 2012)
Abstract Behavioral economics refers to the attempt to increase the explanatory and predictive power of economic theory by providing it with more psychologically plausible fondation. Heath et al dan Ewing (Mittlestaedt, 2002 dalam Hariadi 2011) placed religiusity as a key variable at behavioral economics analysis because has many evidences showing that religiousity has influenced consumer market in many ways. In addition, religiousity is a good predictor of happiness because its ability to make bussinessmen to become more creative, productive and altruistic or on the the contrary. Religiusity is one of most impotance requirements of everyone who is looking for happiness and economis success in modern society, but research of religiusity is not populer at the momnet. In the mid of hedonis culture, people is more interested in pursuing external happiness. In the same vein, psychologist prefer studying external-factors of happines to studying the internal-factors ones . Comparison of number of rising articles for both issues is 17:1 ( Myers Diener, 1995). The research represents an effort to balanced the trend of psychology studies which dig up happiness focusing on depression elimination. The aimed the study to builid a new scale of religiusity and test the model. The data was taken from sample of 277 middle and small entrepreneurs in DIY. The questionaire was built based on the indicators obtained from the literature study. Fitting test of model in the research was done by using structural equation model (SEM) applied maximum likelihood estimates (MLE) method. The result of the test shows that the religiusity model supported by religious-service motif (integrity), the way problem solution (surrenderness), life style, and religious-service need is supported the data ( GFI = 0,951, TLI = 0,981, CFI = 0,989, NFI = 0,984). Keywords: religiusity, religious-service motif, the way problem solution, life style, and religious-service need